Research of the Virtual Machining Method of Vehicle Variable Ratio Gear based on Generation Method - Tan Jiangjiang; Li Gangyan; Niu Ziru; Kong Zhenbin; Hu Dawei (Jixie chuandong)
In order to solve the processing problem of the variable ratio gear（ also called variable ratio gear sector）,a machining method based on generation method is put forward. Combining the transmission theory and the meshing movement characteristics of the variable ratio gear and rack,the machining method for the variable ratio gear is presented and the theory formulas related to the processing of the variable ratio gear by generation method are deduced. In CATIA environment,after establishing rack model conforming to the design parameters of the involute rack and finishing the virtual assembly of the gear pair,the simulating processing of the variable ratio gear by generation method is realized,and the profile modification is carried out. Besides,simulation verification of the variable ratio gear and rack is implemented in ADAMS and the feasibility of this method is verified by the contrastive analysis of the transmission ratio curve got by simulation and the designed transmission ratio curve.